Community-Based Ecotourism in Sawarna Tourism Village - Juliana; Sabrina Oktaria Sihombing; Selvi Esther Suwu (Enrichment : Journal of Management, 2023)
This research is motivated by the importance of developing ecotourism in Sawarna tourism village based on community empowerment to improve the community's economy. The research objective is to determine the development of ecotourism in Sawarna tourism village based on community empowerment. The research approach uses a qualitative approach. There were two participants whose information was investigated by researchers, namely the Chairperson of the Nusantara Tourism Village, Banten Province as Secretary of the Sawarna Tourism Village and the head of the Pokdarwis of the Sawarna Tourism Village. The MOA model is based on theoretical perspectives from a variety of fields, including advertising, consumer behavior, tourism, public participation, and, most recently, event studies. The MOA model's key strength is that it can be applied to destinations with the goal of enabling or facilitating community participation. The MOA model, an already established theoretical framework in the field of tourism, and a desire to understand and document the factors that influence inclusive engagement within local communities inspired this paper. A tourism village built with the concept of community-based tourism is a step for the community to develop their potential to be able to manage their own tourism and make their village an independent village.